Analisis Hasil Pembelajaran Matematika pada Ranah Afektif Mahasiswa Calon Guru di IAIN Purwokerto - Maria Ulpah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Like other lessons, mathematics has learning objectives in affective domain besides in cognitive and psychomotor domain. Formally, this can be seen in the formulation of the objectives of mathematics learning, as stated in the curriculum. The success of learning in cognitive and psychomotor is strongly influenced by students' affective condition. Students who have a good interest in learning and a positive attitude towards mathematics will be happy to learn math, so optimal learning outcomes can be achieved. Students of Tarbiya Faculty as prospective teachers should have good affective in order not to complicate students in the future. This article describe about students’ affective in mathematics. According to the data, it can be concluded that students’ affective is good. This condition must be nurtured and enhanced.